Infraestructuras para la vida cotidiana y calidad de vida - Inés Sánchez de Madariaga (Ciudades, 2004)
In western countries, transformation of relationship between genres, and transformation of the traditional sexual division of work, has completely disrupted family support services and, especially, those ones, directed to dependant people. On the other hand, in social and urban politics, the answer to this challenge is being very weak and very different from one country to another, being women, in particular, the ones who need more clearly, specific spatial necessities on the different scales and sectorial aspects of urbanism. This article defines the concepts of “enew veryday life” and “infrastructures for everyday life”, and analyzes their historical background and illustrates them with contemporary experiences. The article ends up with a critical reflection about the Spanish case.